طرق الطعن في الأحكام القضائية في المادة الجزائية - هناء بوعلي; مريم صاحي (My University, 2025)
Summary in English: This thesis addresses the means of appeal against criminal judicial rulings، aimed at ensuring justice and correcting judicial errors. Appeals are classified intro: - Ordinary appeals: Such as opposition and appeal، used before the ruling becomes final. - Extraordinary appeals: Such as cassation and retrial، used in exceptional circumstances against final judgments. The thesis outlines the legal conditions، procedures، and deadlines for each appeal type and analyzes their impact on the execution of the ruling. It also includes case law and practical applications. ............................. ملخص: تتناول هذه المذكرة طرق الطعن في الأحكام القضائية الجزائية، والتي تهدف إلى ضمان عدالة الحكم وتصحيحه عند الخطأ. وتنقسم طرق الطعن إلى: طرق طعن عادية: مثل الاستئناف والمعارضة، وهي طرق يمكن استعمالها قبل أن يصبح الحكم نهائياً. طرق طعن غير عادية: مثل النقض وإعادة النظر، وهي تُستعمل ضد الأحكام النهائية في حالات استثنائية. توضح المذكرة الشروط والإجراءات القانونية لكل طريقة طعن، والمواعيد المحددة لها بالإضافة إلى آثار كل طعن على تنفيذ الحكم. كما تستعرض اجتهادات القضاء والتطبيقات العملية. ......................... Résumé en français : Ce mémoire traite des voies de recours contre les jugements en matière pénale، dans le but d’assurer la justice et de corriger les erreurs judiciaires. Ces recours sont divisés en : - Recours ordinaires : comme l'opposition et l'appel، qui peuvent être utilisés avant que le jugement ne devienne définitif. - Recours extraordinaires : comme le pourvoi en cassation et la révision، utilisés dans des cas exceptionnels contre les jugements définitifs. Le mémoire décrit les conditions légales، les procédures et les délais pour chaque type de recours، ainsi que leurs effets sur l’exécution du jugement. Il inclut également des exemples jurisprudentiels et des applications pratiques.
Keywords: Keywords: methods of Appeal; Criminal Judgments; Ordinary Appeal; Extraordinary Appeal; Review; الكلمات المفتاحية: طرق الطعن،الأحكام الجزائية،الطعن العادي،الطعن غير العادي،النقض; Mots-clés : Voies de recours; Jugements pénaux; Recours ordinaires; Recours extraordinaire; révision